2017
DOI: 10.1002/joc.5206
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of temperature changes in Western China

Abstract: Western China (WC) is located in the arid and semi-arid belt of the mid-latitudes. Understanding the causes of the large temperature increases experienced in this region is of great importance because both the fragile ecological environment and the human societies in WC are highly vulnerable to changes in climate. We conducted a detection and attribution analysis on the annual mean temperature using an optimal fingerprinting method by comparing observations based on homogenized station data with simulations co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…The resulting station anomalies are aggregated to 58 3 58 grid cell anomalies by averaging all available station anomalies within a predefined grid cell. This gridcell system, which has also been used in previous studies investigating near-surface air temperature changes in China (e.g., Sun et al 2014;Wang et al 2017), allows relatively accurate estimates of spatial averages from uneven station observations. Grid cells with 44 (80%) or more years of data during 1961-2015 are retained for subsequent analysis.…”
Section: Data and Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting station anomalies are aggregated to 58 3 58 grid cell anomalies by averaging all available station anomalies within a predefined grid cell. This gridcell system, which has also been used in previous studies investigating near-surface air temperature changes in China (e.g., Sun et al 2014;Wang et al 2017), allows relatively accurate estimates of spatial averages from uneven station observations. Grid cells with 44 (80%) or more years of data during 1961-2015 are retained for subsequent analysis.…”
Section: Data and Preprocessingmentioning
confidence: 99%
“…Significant increases in summer mean temperature since the mid-twentieth century in China have been observed and attributed to human influence (Ren et al 2012;Sun et al 2014;Wang et al 2017). For example, it is reported that human influence has made the recordbreaking hot summer of 2013 in eastern China more than 60 times as likely as it would have been in a natural world without human influence (Sun et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection and attribution studies based on model simulations provide a useful way in understanding the relative contribution of internal climate variability and different external forcings to the observed climate change. Meanwhile, attribution results can correct the overestimation (underestimation) of model simulations, providing more reasonable information of future projection (Allen et al 2000;Wang et al 2018). Results based on the detection and attribution studies conclude that "It is extremely likely that human influence has been the dominant cause of the observed warming since the mid-twentieth century" (IPCC 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although detection and attribution studies should be more difficult at a smaller region because of the lower ratio of signal to noise (Stott et al 2010;Hegerl and Zwiers 2011), increasing evidence demonstrate human influence on the changes in regional mean and extreme temperature (Wen et al 2013;Zhou et al 2014;Sun et al 2014Sun et al , 2016aXu et al 2015;Lu et al 2016;Ma et al 2017a;Yin et al 2017;Wang et al 2018). The observed increases in annual mean temperature (Xu et al 2015;Sun et al 2016b), intensity of extreme temperature (Wen et al 2013;Yin et al 2017), and frequency of extreme temperature (Lu et al 2016) in China during the past half century are attributable to anthropogenic forcings.…”
Section: Introductionmentioning
confidence: 99%